2014
DOI: 10.1007/s00592-014-0660-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of screening for gestational diabetes mellitus by oral glucose tolerance tests done in the non-fasting (random) and fasting states

Abstract: Aim The Diabetes in Pregnancy Study Group of India (DIPSI) guidelines recommend the non-fasting 75-g oral glucose tolerance test (OGTT) as a single-step screening and diagnostic test for gestational diabetes mellitus (GDM). The aim of this study was to compare the DIPSI criteria with the World Health Organization (WHO) 1999 and the International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria for GDM.MethodsA total of 1,031 pregnant women attending antenatal clinics in urban and rural Tami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
91
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 12 publications
6
91
1
1
Order By: Relevance
“…The diagnostic rate of GDM based only on the fasting value was 8.43%. This also correlates with the findings of other studies [11,16]. Our study shows thatFBG value has the highest diagnostic rate for GDM which is being completely ignored by DIPSI.We further assessed the severity of GDM by dividing the patients into two groups, one on MNT alone and the other requiring some form of pharmacotherapy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The diagnostic rate of GDM based only on the fasting value was 8.43%. This also correlates with the findings of other studies [11,16]. Our study shows thatFBG value has the highest diagnostic rate for GDM which is being completely ignored by DIPSI.We further assessed the severity of GDM by dividing the patients into two groups, one on MNT alone and the other requiring some form of pharmacotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…A comparison of these studies is shown in Table 5. In our study, the total number of patients diagnosed to be GDM by IADPSGwas 11.97%, which is comparable to the study by V Mohan et al [16]. By DIPSI criteria, using only the 2hr value, GDM was diagnosed in 3.94% cases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There are other studies showing poor sensitivity of GCT in diagnosing GDM (19,20). A recent study conducted by V Mohan, et al in India showed a very low sensitivity of non-fasting GCT when compared to the IADPSG criteria (sensitivity 22.6%, specificity 97.8%) (21). Other studies done in South Asian ethnicity as well as in Caucasians too have revealed poor sensitivity of 50g and 75g GCT (19,22,23).…”
Section: Discussionmentioning
confidence: 97%
“…Women in India with GDM Strategy (WINGS) while validating the non fasting DIPSI criteria, found that it has very low sensitivity (27.7%) compared to the WHO criteria and even lower sensitivity in comparison with IADPSG criteria (22.6%) although specificity was quite high. 17 A study from Delhi similarly reported that the no fasting DIPSI criteria results in low sensitivity. 18 Thus two independent studies from different geographic locations showed that the DIPSI no fasting OGTT is not suitable as a diagnostic test as it can miss a considerable number of women with GDM.…”
Section: Discussionmentioning
confidence: 99%